EVOLUSI HUKUM KELUARGA ISLAM SEBELUM DAN SELAMA ERA REVOLUSI INDUSTRI 5.0 - Sugitanata, Arif; Adnan, Idul; Hartawan, Hartawan; Muzawir, Muzawir (Al-Muqaronah: Jurnal Perbandingan Madzhab dan Hukum, 2022)
The Industrial Revolution 5.0 changed the paradigm of human interaction with technology, which emphasises the synergy between artificial intelligence and unique human capabilities to create more humane and sustainable innovations. In the context of Islamic family law, the Industrial Revolution 5.0 brings new challenges and opportunities that require thoughtful understanding to ensure its relevance and benefits for Muslims. This research compares the evolution of Islamic family law before and during the Industrial Revolution 5.0 era through a literature study-based comparative approach with a qualitative research type. The research shows that, before the revolution, Islamic family law had established a solid moral and social foundation, regulating marriage, divorce, inheritance and family responsibilities with an emphasis on social justice and the protection of individual rights. When the Islamic family law entered the revolutionary era, significant changes were encountered in communication, employment, family economy, and education. Although new technology has brought opportunities to strengthen faith and religious practice, it has also raised issues such as privacy and psychological impact. Islamic family law is required to integrate traditional values with technological innovations, maintain education and understanding of rights and obligations within the family, and maintain a balance between material and spiritual progress. With judicious adaptation, Islamic family law can ensure harmonious and prosperous families in this new era.